The Demonic Genius of Politics? Social Action and the Decoupling of Politics from Violence - Pearce, Jenny (International Journal of Conflict and Violence (IJCV), 2017)
This paper explores why new ways of “knowing” and acting on violence could lead to a reconsideration of Weber’s pessimistic coupling of politics and violence. This coupling remains hugely influential almost a century after it was formulated. It has become possible to revisit it, firstly, because of the potential for new interdisciplinary conversations. These have opened up ways of understanding violence as a properly social phenomenon and the significance of our vulnerable, social bodies to its reproduction. Secondly, social action on violence has led to recognition as “violence” of varied acts of somatic harm previously not named as such. In the process, expressions of violence reproduced over time and through spaces of socialization (from the intimate to the construction of the nation state) are socially and politically de-sanctioned. Politics and the State could be reconceptualised as essential for reducing (rather than monopolizing) violence and creating conditions to live together without it.